Occurrence of Lutzomyia longipalpis (Phlebotominae) and canine visceral leishmaniasis in a rural area of Ilha Solteira, SP, Brazil - Pereira Spada, Julio Cesar [UNESP]; Silva, Diogo Tiago da [UNESP]; Real Martins, Kennya Rozy; Rodas, Lilian Aparecida Colebrusco; Alves, Maria Luana [UNESP]; Faria, Glaucia Amorim [UNESP]; Buzutti, Marcelo Costa [UNESP]; Silva, Helio Ricardo [UNESP]; Starke-Buzetti, Wilma Aparecida [UNESP] (Brazilian Coll Veterinary Parasitology, 2014)
This study aimed to investigate the occurrence of Lutzomyia longipalpis and also the canine visceral leishmaniasis (CVL) in a rural area of Ilha Solteira, state of Sao Paulo. Blood samples were collected from 32 dogs from different rural properties (small farms) and were analyzed by ELISA and the indirect immunofluorescence antibody test (IFAT) in order to diagnose CVL. From these serological tests, 31.25% of the dogs were positive for CVL and these were distributed in 66.7% (8/12) of the rural properties, which were positive for L. longipalpis. CDC (Center for Disease Control and Prevention) light traps were installed in 12 properties (one per property) and insects were caught on three consecutive days per month for one year. L. longipalpis was present on 100% of the rural properties visited, at least once during the twelve-month interval, totaling 64 males and 25 females. The insects were more numerous after the peak of the rain, but the association between prevalence of peridomestic vectors and the climatic data (precipitation, relative air humidity and temperature) and the occurrences of CVL among dogs on each rural property were not statistical significant (p < 0.05). However, the occurrence of CVL cases in dogs and the presence of L. longipalpis indicate that more attention is necessairy for the control of this disease in the rural area studied.

O objetivo desse trabalho foi o estudo da prevalência de Lutzomyia longipalpis e da leishmaniose visceral canina (LVC) em uma área rural do município de Ilha Solteira do estado de São Paulo. Amostras de sangue foram coletadas de 32 cães provenientes de pequenas propriedades rurais e analisadas por meio dos métodos sorológicos ELISA (imunoensaio enzimático indireto) e RIFI (reação de imunofluorescência indireta) para o diagnóstico da LVC. Pelos exames sorológicos, dos 32 cães avaliados, 31,25% foram diagnosticados positivos para LVC, os quais estavam diostribuídos em 66,67% (8/12) das propriedades positivas para Lutzomyia longipalpis. Armadilhas luminosas do tipo CDC (Center for Disease Control and Prevention) foram instaladas em 12 propriedades, sendo uma por propriedade, e as coletas dos insetos foram realizadas três dias consecutivos a cada mês, durante um ano. O inseto L. longipalpis foi encontrado em 100% das propriedades visitadas, pelo menos uma vez no ano, totalizando 65 machos e 25 fêmeas. A maior quantidade de insetos foi observada principalmente após a ocorrência dos maiores picos de precipitação pluvial, mas a associação entre a prevalência dos vetores peridomiciliares e os dados climáticos (precipitação, umidade relativa do ar e temperatura) assim como a ocorrência da CVL em cães em cada propriedade não foi estatisticamente significante (p<0.05). No entanto, alerta-se que pela presença dos casos de LVC nos cães amostrados e também de L. longipalpis, maior atenção deve ser dada durante as investigações epidemiológicas para o controle dessa doença nessa área rural estudada.
Keywords: CDC; ELISA; IFAT; Leishmania infantum; Lutzomyia longipalpis